The effects of ground surface materials towards the microclimate of parking lots in IIUM Gombak - Omar, Mardhiyatul Farahin; Zulkefle, Nuur Aini; Abu Bakar, Aniza (2015)
Urban Heat Island (UHI) phenomenon gives negative impacts towards urban climate changes, energy use and rises on the temperature of cities. One of the factors that contribute to the rising of temperature in urban area is the significant amount of impervious surfaces. The use of impervious surfaces is mostly found in parking lots which could create hotspots as impervious surfaces like tarmac absorb greatly amount of heat. To counterbalance the impacts of UHI, several mitigation techniques have been developed and applied including green technology towards sustainable environment such as the application of pervious surfaces. The study focused on the effects of ground surface materials at parking lots and their landscape setting towards microclimate. The methods for this study were conducted through case study, observation and environmental data collection at parking lots in International Islamic University Malaysia (IIUM). The case study sites were categorized into two namely impervious and pervious surfaces. Two sites were identified for each category whereby one site had plenty greenery and the other one had less greenery. The variables that took into consideration for this study were surface temperature (oC), solar radiation (w/m2), air temperature (oC), relative humidity (%), wind environment (m/s) and sky condition (oktas). The result suggested that parking lot with pervious surfaces and plenty greenery presenting lower surface temperature and cooling the surrounding environment.